Physiological Effects of Some Pollen Substitutes Diets on Caged Honey Bee Workers (Apis mellifera L.) - Amro, Abdulraouf; Younis, Mohamed; Ghania, Ayman (International Journal of Environment, 2020)
Nutritional value of four proteinaceous diets and their physiological effects on honey bee workers were evaluated under laboratory conditions. The tested diets were as follows: diet 1 – date (Phoenix dactylifera L.) syrup, skimmed milk powder and dried brewer's yeast, diet 2 – Fenugreek (Trigonella foenum-graecum L.), Turmeric (Curcuma longa L.) powders and dried brewer's yeast, diet 3 – chickpea (Cicer arietinum L.) flour, wheat germ and dried brewer's yeast and diet 4 - soybean meal, skimmed milk powder and dried brewer's yeast, beside a control group (bee bread). Caged Carniolan honey bee workers were used in the experiments. The consumption rate, workers longevity, development degree of hypopharyngeal glands (HPG), and weight of rectal contents were determined. The greatest consumption rate was recorded for the control group while the lowest one was recorded for diet 4. Feeding bees on diet 3 gave the longest longevity (LT50= 27.0 days) among the tested diets and as a second rank after bees in the control group (LT50 = 29.0 days) while diet 4 showed the lowest longevity (LT50 =20.5 days). The highest HPG development degree (3.78) was recorded for 9 days old bees in the control group, followed by diet 3 (3.24) while the lowest degree (2.14) was to diet 4. The weight of rectal contents of honey bee workers was 13.43, 16.03 and 16.12 mg/bee/3 days for diet 3, diet 1 and diet 2, respectively, suggesting the suitability of these diets to bees. In light of this study, diet 3 and 2 have the best physiological effects for bees with good nutritional values.